Patterned hydrodynamic slip flow control and thermal transport in a wavy microchannel through porous medium with combined Electromagnetohydrodynamic effect. Issue 1 (March 2021) - Rana, Amalendu; Shit, Gopal Chandra; Reza, Motahar
Abstract: A conceptual exploration is conducted to analyze the numerical experiment of the pattern hydrodynamic slip flow control and thermo-fluidic transport features coupled with the influence of the combined electromagnetohydrodynamic (EMHD) effect in a wavy microchannel through the porous medium. The constitutive equations for the velocity distribution and energy distribution are represented by a set of non-linear differential equations. These equations are solved numerically by employing a shooting technique based on the fourth-order Runge-Kutta method. The effect of Joule heating and temperature jump on the temperature distribution is also discussed in this study. The significant impacts of the electromagnetic force, the porosity of medium, Forchhemier inertia parameter, the impression of the wavy-walls amplitude, the effect of the wavenumber of the slip length on momentum, and thermal transport are discussed in this investigation. It is revealed that the velocity and the temperature both are augmented with the improvement of the amplitude of the wavy wall of the microchannel but the wave number of the slip length minimize the velocity as well as the temperature of the fluid.